Successful endovascular reconstruction of symptomatic vertebrobasilar dolichoectasia using multiple Leo stents and nondominant vertebral artery occlusion: a case report - Soetanto, Gamaliel Wibowo; Ganiem, Ahmad Rizal; Adam, Achmad; Lilikwatil, Pieter Melchias Jacob; Usman, Fritz Sumantri (International Journal of Research in Medical Sciences, 2024)
Vertebrobasilar dolichoectasia (VBD) is a rare vascular anomaly of increased diameter, length, and tortuosity of vertebral and/or basilar artery, but debilitating due to its risk of ischemia, hemorrhage, and nerve or brain compression. The management is also controversial due to various possible clinical manifestation and outcome. This study aimed to describe a combined approach of multiple scaffolding Leo stents and nondominant vertebral artery occlusion as a definitive approach to reconstruct vertebrobasilar arteries. A 40-year old male presented with severe headache and reduced consciousness, which was explained with brain CT findings of subarachnoid hemorrhage and hydrocephalus. Further etiologic approach until digital subtraction angiography revealed VBD. An endovascular reconstruction approach was considered one month following the event onset using multiple scaffolding Leo stents from left vertebral to basilar artery with right vertebral artery occlusion. This stent had the best radial strength, lowest bending stiffness, highest kink resistance, highest bending wall coverage, and lowest cell size, which provided strong vascular reconstruction properties. Combined nondominant vertebral artery occlusion was also performed to avoid the disturbance of flow-diverting pathway by the stents. Double antiplatelet was administered from three weeks following the event onset afterwards. The patient’s condition improved at three-month follow-up. This case report presented that combined multiple Leo stents and nondominant vertebral artery occlusion may be considered as an approach to successful endovascular reconstruction for symptomatic VBD.